ANALISIS HASIL BELAJAR SISWA MELALUI PENDEKATAN KONSEP REALISTIC MATHEMATIC EDUCATION (RME) PADA MATERI FPB DAN KPK DI KELAS IV SD - Lubis, Aminah; Surya, Edy; Fauzi, Muhammad Amin (Universitas Negeri Medan, 2024)
When students have trouble with mathematical concepts, it shows in their low learning outcomes. This classroom action research project aims to examine the potential of a multi-function board in enhancing teacher and student engagement and learning outcomes related to FPB and KPK content through the implementation of the Realistic Mathematics Education method. Classroom action research is a method used in this study. Participants in the study were fourth graders. The researcher in this study is also the classroom instructor, and the class teacher acts as an observer of the KPK and FPB lessons. Findings from this study demonstrate that fourth graders at SDN 0701 are making good use of Realistic Mathematical Education (RME) to enhance their understanding of KPK and FPB content and to foster their creative thinking. Higher levels of teacher engagement and student achievement are indicators that the educator has implemented the pedagogical practices outlined in the Realistic Mathematical Education model. Thus, in order to maximise student learning results and foster optimal creative development, it is recommended that teachers implement the Realistic Mathematical Education (RME) paradigm while teaching mathematics on KPK and FPB content.